HUBUNGAN SIKLUS MENSTRUASI DAN KECEMASAN TERHADAP PERFORMA ATLET WANITA DI CLUB TAEKWONDO KARO - Agita Karina Waruwu; Tri Widia Astuti Tamba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the menstrual cycle and anxiety on the performance of female athletes at the Karo Taekwondo Club. Performance of female athletes is influenced by various physiological and psychological factors, including hormonal changes during the menstrual cycle and anxiety levels during training or competition. This research uses a quantitative method with a correlational design. The population consisted of 35 female athletes, with a sample of 15 respondents selected using purposive sampling technique. Data were collected using a menstrual cycle questionnaire, the CSAI-2 anxiety instrument, and physical performance tests covering strength, speed, agility, and endurance. Data analysis used correlation and regression tests. The results showed a significant positive relationship between the menstrual cycle and performance (r = 0.809; p < 0.01), a significant negative relationship between the menstrual cycle and anxiety (r = -0.557; p < 0.05), and a negative but not significant relationship between anxiety and performance (r = -0.419; p > 0.05). It is concluded that regular menstrual cycles support optimal physical conditions, while hormonal fluctuations increase susceptibility to anxiety. Coaches are expected to design training programs adapted to the physiological and psychological conditions of female athletes.